TANTANGAN EKONOMI PRESIDEN TERPILIH 2009: SELAMATKAN PEREKONOMIAN NASIONAL DARI ANCAMAN KRISIS KEUANGAN GLOBAL - Ulum, Ihyaul (Jurnal Bestari, 2009)
The president of 2009-2014 will face a difficult challenge. Beside the rise of stronger opposition power in the parliament, there are also so many various economic problems. Poverty, unemployement, foreign debt, and stack of macro economic problems that become worse because of global monetary crisis becomes a hard task to save the national economic matters from the effect of the crisis.